Carcinosarcoma of Uterus A highly Aggressive Tumour A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Carcinosarcoma (CS) of uterus is a relatively rare tumour and accounts for less than 1 percent of malignant growth of the female genital tract. This tumour contains both malignant epithelial component and malignant stromal component. So, it is also known as malignant mixed mullerian tumours (MMMTS). Carcinosarcoma usually arise from endometrium and myometrium and rarely from cervix, ovary. The clinical presentation is mostly postmenopausal bleeding but enlarging pelvic mass, pelvic pain, vaginal discharge or polypoidal mass protruding through the cervical os are also frequently present. The risk factors include obesity, exogenous estrogen, nulliparity, exposure to radiation & temoxifen. Histological evaluation by endometrial biopsy will establish the diagnosis in most cases. Carcinosarcoma is aggressive type of tumour; extra-uterine spread is very common and generally carries a poor prognosis. The prognosis depends on the extent of the tumour at the time of primary surgery. This case report describes a rare type of presentation of the tumour which arose from the body & cervix of uterus and presented with a polypoidal mass prolapsed into the vagina. The case was properly diagnosed & managed by surgery and postoperative adjuvant radiotherapy. DOI: http://dx.doi.org/10.3329/bjog.v25i1.13730 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 33-36